2015
DOI: 10.14573/altex.1503051
|View full text |Cite
|
Sign up to set email alerts
|

Development and characterization of an ex vivo arterial long-term proliferation model for restenosis research

Abstract: SummaryOne of the main limitations of percutaneous coronary interventions is restenosis, occurring in small-diameter arteries. Many efforts are underway to find improved intracoronary devices to prevent in-stent restenosis. The aim of this study was to produce a new in vitro test platform for restenosis research, suitable for long-term cell proliferation and migration studies in stented vessels. Fresh segments of porcine coronary arteries were obtained for decellularization and were then reseeded with human co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Interestingly, we did not detect a critical difference in lumen coverage, apoptosis or activation of the vessel wall in the two culture systems. This is not completely unexpected as the static culture was designed to replicate the vessel ring culture, with tissue specimens of 2-5mm in length (5,21-23). Previous studies have demonstrated that static culture of rings can be extended up to 56 days, and can be induced to form neointima post-injury, although we did not detect such a growth in our samples (22).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, we did not detect a critical difference in lumen coverage, apoptosis or activation of the vessel wall in the two culture systems. This is not completely unexpected as the static culture was designed to replicate the vessel ring culture, with tissue specimens of 2-5mm in length (5,21-23). Previous studies have demonstrated that static culture of rings can be extended up to 56 days, and can be induced to form neointima post-injury, although we did not detect such a growth in our samples (22).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, we did not detect a critical difference in lumen coverage, apoptosis or activation of the vessel wall in the two culture systems. This is not completely unexpected as the static culture was designed to replicate the vessel ring culture, with tissue specimens of 2–5 mm in length ( 5 , 23 25 ). Previous studies have demonstrated that static culture of rings can be extended up to 56 days, and can be induced to form neointima post-injury, although we did not detect such a growth in our samples ( 24 ).…”
Section: Discussionmentioning
confidence: 99%